Response of Indonesia’s Fisheries GDP to Interest Rates, Inflation, Exchange Rates, and Fisheries Sector Performance: A Blue Economy Perspective - Ayu Dwi Pitaloka, Dyah; Herlina, Deswita; Suci, Stannia Cahaya; Harahap, Muhammad Nasim (Jurnal Ilmu Manajemen dan Ekonomika, 2025)
This study analyzes how Indonesia’s fisheries GDP (FISHGDP) responds to real interest rate, inflation, exchange rate, fisheries production, and exports within the Blue Economy framework. Using VECM and data from 1985–2024, it examines short- and long-term relationships through IRF and Variance Decomposition. Results show fisheries’ GDP responds positively to inflation, production, and exports, but negatively to exchange rates, with mixed responses to interest rates. In the long term, FISHGDP variation is mainly explained by its own past values (80.14%), followed by fisheries production (7.71%), interest rate (6.50%), exchange rate (4.94%), inflation (1.09%), and exports (0.77%). This highlights the key role of macroeconomic stability and fisheries productivity for Indonesia’s Blue Economy growth.